SYSTEMES DE RECOMMANDATION BASES SUR L'APPRENTISSAGE AUTOMATIQUE - Isra Mallek Feknous (My University, 2023)
Recommender systems play a crucial role in helping users discover relevant items in à vast sea ofinformation.Overtheyears,varioustechniqueshavebeendevelopedtoenhancetheaccuracyandeffectiveness of recommendation algorithms. One approach that has gained significant attention is thehybrid recommender system, which combines multiple recommendation techniques to providemoreaccurate and personalized recommendations.Hybrid recommender systems leverage the strengths ofdifferent recommendation approaches, such as collaborative filtering, content-based filtering, knowledge-basedfiltering, andcontext-awarefiltering. In this work we have presented a proposal for a recommendation system based on machine learning. Wemainlyfocusonusinguser-basedcollaborativefilteringandhybridapproachestogeneraterecommendationsbyanalyzingsimilarities betweenusers in the MovieLensdatabase. The main idea behind the development of our recommender system is to apply k-means clustering topersonalizerecommendations, whileusingthe CNN classifierto improvepredictions. This method offers the advantage of combining two learnings both machine learning for clustering anddeeplearningforclassification, which allows to obtainaccurate results. ----------------------------------------------------------------------------------------- تلعب أنظمة التوصية دورًا مهمًا في مساعدة المستخدمين على اكتشاف العناصر ذات الصلة في بحر شاسع من المعلومات. على مر السنين، تم تطوير تقنيات مختلفة لتعزيز دقة وفعالية خوارزميات التوصية. ومن أحد الأساليب التي حظيت باهتمام كبير هو نظام التوصية الهجين، الذي يجمع بين تقنيات توصية متعددة لتقديم توصيات أكثر دقة وشخصية. تستفيد أنظمة التوصية المختلطة من نقاط القوة في مناهج التوصية المختلفة، مثل التصفية التعاونية، والتصفية القائمة على المحتوى، والتصفية القائمة على المعرفة، والتصفية المدركة للسياق. في هذا العمل، قدمنا اقتراحًا لنظام توصية يعتمد على التعلم الآلي. حيث ركزنا بشكل أساسي على استخدام أساليب التصفية التعاونية القائمة على المستخدم والمقاربات الهجينة لإنشاء توصيات من خلال تحليل أوجه التشابه بين المستخدمين في قاعدة بيانات “MovieLens” الفكرة الرئيسية وراء تطوير نظام التوصية الخاص بنا هي تطبيق مجموعة الوسائل “k_means” لتخصيص التوصيات، أثناء استخدام مصنف CNN لتحسين التنبؤات. توفر هذه الطريقة ميزة الجمع بين تعلمتين كل من التعلم الآلي للتجميع والتعلم العميق من أجل التصنيف ، مما يسمح بالحصول على نتائج دقيقة. ------------------------------------------------------------------------------------------ Les systèmes de recommandation jouent un rôle crucial dans l'aide aux utilisateurs pour découvrir deséléments pertinents dans une vaste quantité d'informations. Au fil des ans, différentes techniques ont étédéveloppées pour améliorer la précision et l'efficacité des algorithmes de recommandation. Une approchequi a suscité beaucoup d'attention est le système de recommandation hybride, qui combine plusieurstechniques de recommandation pour fournir des recommandations plus précises et personnalisées. Lessystèmesderecommandationhybridesexploitentlespointsfortsdedifférentesapprochesderecommandation, telles que le filtrage collaboratif, le filtrage basé sur le contenu, le filtrage basé sur lesconnaissanceset lefiltragebasésur lecontexte. Danscetravailnousavonsprésenteunepropositiondesystèmederecommandationbasésurl'apprentissageautomatique.Nousnousconcentronsprincipalementsurl'utilisationdufiltragecollaboratifbasésurl'utilisateuretdesapprocheshybridespourgénérerdesrecommandationsenanalysantles similarités entreles utilisateurs dansla basededonnées MovieLens. L'idéeprincipalederrièreledéveloppementdenotresystèmederecommandationestd'appliquerleclustering k-means pour personnaliser les recommandations, tout en utilisant le classificateur CNN pouraméliorerlesprédictions.Cetteméthodeoffrel'avantagedecombinerdeuxapprentissageàlafoisl'apprentissage automatique pour le clustering et l'apprentissage profond pour la classification, ce quipermetd'obtenirdesrésultats précis.